Cerebral Metastasis as First Systemic Event in a Patient with Prostate Adenocarcinoma - Reinas, Rui; Costa, Pedro; Baggen Santos, Raul; Kitumba, Djamel; Furtado, Antónia; Espiridião, Paulo; Baptista, António Marques; Silva, Luís Ferraz; Alves, Óscar L. (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Prostate adenocarcinoma (PAC) is the second most common malignant tumor in men, and it is usually diagnosed because of its symptoms and/or because of an increase in the value of the prostate-specific antigen (PSA) in asymptomatic patients. The lymph nodes and the bones are the most common sites in which metastases occur, while the brain is a rare site, with metastases occurring in < 2% of the cases, and usually only after the aforementioned sites have been affected. Considering the brain as the only site where a metastasis can occur, the incidence is of 0.15%. We present the case of a 63-year-old male diagnosed with PAC, with a Gleason score of 7 (3+4), who underwent radiotherapy and anti-hormonal therapy in 2012. After biochemical recurrence early in 2015 (PSA: 8 ng/mL), he was re-staged, and the bone and node metastases were excluded. The patient then resumed the hormone therapy with bicalutamide. He was admitted in August 2015 to the emergency department of our institution with headache and behavioral changes. The imaging study revealed a single right temporo-parieto-occipital lesion, which was then resected. The histological analysis confirmed it to be a PAC brain metastasis. The patient went through a cycle of brain radiotherapy, and evolved favorably after one year of follow-up.
Keywords: prostatic neoplasms; brain tumors; neoplasm metastasis